ШАХСНИНГ КАСБИЙ КАРЬЕРАСИГА ТАЪСИР ЭТУВЧИ ФАКТОРЛАР МУАММО ВА ЕЧИМЛАР - Холйигитова, Н.Х. (SCIENCE and SOCIETY, 2025)
The article analyzes the main socio-psychological, economic and educational factors affecting the professional career of an individual. In the process of career development is based the importance of personal abilities, family environment, quality of Education, supply and demand in the labor market, psychological support factors.
Keywords: Professional career; Personality Development; Career Choice; labor market; motivation; educational impact; professional orientation